Strengthening the Religious Moderation Literacy Model in the Implementation of the Independent Curriculum (IKM) - Imam Mas Arum; Guntur Cahyono (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
Strengthening religious moderation literacy is one of the important efforts in strengthening the spirit of diversity and tolerance in Indonesia. The ability to access, understand, and utilize information is an important foundation in a balanced moderation attitude. Along with strengthening religious moderation literacy in education units and the implementation of the independent curriculum, the synergy between the two is becoming increasingly important. Each educational unit has its own unique curriculum and characteristics. This research is carried out through a descriptive qualitative approach by tracing religious literacy and local wisdom in the community that has a part in strengthening religious moderation. In this case, the researcher will further examine religious moderation literacy in the independent learning curriculum at SMK ITSI Surakarta. In the context of 21st century learning, learning that applies religious moderation literacy continues to be developed to achieve the Pancasila student profile. Concrete actions to overcome obstacles in strengthening the religious literacy model in the implementation of the independent curriculum at SMK ITSI Surakarta include strengthening human resources, self-training/IHT, proposing fees to the Foundation, prohibiting students from bringing cellphones in schools/dormitories, and strengthening moderate and tolerant religious literacy.Keywords: Literacy, Moderation, Implementation of the Independent Curriculum (IKM)